EFFORTS TO IMPROVE CHILDREN'S INTEREST IN READING THROUGH COMMUNITY READING PARK IN UJAN MAS DISTRICT, KEPAHIANG REGENCY - Rodin, Rhoni (Publication Library and Information Science, 2022)
The condition of Indonesian people's interest in reading is still apprehensive. The love of reading has not been well entrenched in society. The purpose of this study was to analyze how to increase children's interest in reading through community reading gardens in Ujan Mas District, Kepahiang Regency. The approach used in this research is a qualitative approach and the research method used is a qualitative descriptive research method. Data were collected by observation, interviews and documentation. The results of the study show that 1) The formation of reading habits should start as early as possible in life, namely from childhood. Cultivating a love of reading should be a shared responsibility. The benefits of reading for the community are very important to add and enrich thinking and broaden knowledge. The public can use the library as a suggestion to get various information and knowledge needed. Libraries as information resource centers and learning resource centers can take various practical and applicable steps to cultivate people's love of reading. In this way, the hope of realizing an intelligent and quality society will be realized; 2) Efforts by the Management of Community Reading Parks in fostering interest in reading are carried out by planning programs by identifying needs, implementing programs, integrating learning with reading activities in Community Reading Parks, and improving the facilities and infrastructure owned by Community Reading Parks so that they can be utilized effectively. directly by the community.